Correlating field and laboratory investigations for preventing ASR in concrete – The LNEC cube study (Part I – Project plan and laboratory results). (8th August 2022) - Custódio, João; Lindgård, Jan; Fournier, Benoit; Santos Silva, António; Thomas, Michael D.A.; Drimalas, Thanos; Ideker, Jason H.; Martin, Renaud-Pierre; Borchers, Ingmar; Johannes Wigum, Børge; Rønning, Terje F.
Highlights: Effect of fly ash in controlling ASR expansion with highly reactive aggregates. Long-term performance of fly ash in controlling expansion due to ASR in concrete. Environmental conditions influence on ASR development in concrete. Environmental conditions influence on ASR mitigation with fly ash in concrete. Correlation between laboratory accelerated concrete prism test results and field behaviour. Abstract: As part of the Norwegian R&D project "ASR - Reliable concept for performance testing (KPN-ASR)" and of the RILEM TC 258-AAA activities, a study was launched in 2015 with the aim of correlating the results of field and laboratory investigations for selecting appropriate preventive measures against deleterious alkali-silica reaction (ASR) in concrete. Three coarse aggregates, i.e. New Mexico polymictic gravel, Ottersbo cataclasite, and a non-reactive limestone aggregate, were used to manufacture cubes (300×300×300 mm 3 ) from air-entrained, control (high-alkali cement; normal alkali cement) and ASTM Class F fly ash (20 and 30 % replacement levels of the high-alkali cement) concrete mixtures. The cubes were then shipped to be placed on the study participants' outdoor exposure sites, where they are being monitored for long-term expansion and cracking development (Canada; France; Germany; Iceland; Norway; Portugal; USA). Companion laboratory cubic specimens (for compressive strength and air-void spacing factor determination on hardened concrete) and test prisms were cast from the above mixtures. The prisms were subjected to RILEM AAR–3.1 and RILEM AAR-4.1 testing at LNEC's laboratory; their expansion was monitored over 205 and 28 weeks, respectively. Selected control and fly ash mixtures, without air-entrainment, were repeated at SINTEF following the 38 °C Norwegian concrete prism test (NCPT, prism size 100×100×450 mm 3 ) and RILEM AAR-4.1. This paper, the first of the LNEC cube study, gives an overview of the project, lists the project's main objectives, provides a summary of the activities already developed in the project, and presents and discusses the results obtained thus far in the laboratory investigations. As expected, excessive expansions were obtained for the control high-alkali concretes, whereas addition of fly ash reduced the expansion to a low level. However, the expansion attained for the fly ash mixtures depended on the CPT procedure used.